'I found this written in the other book': Learning Astronomy in Late Medieval Monasteries. (3rd June 2019) - Falk, Seb
Abstract : Recent histories have challenged narratives of a late medieval decline in monastic scholarship. This article extends that work to the natural sciences, showing how monks could learn astronomy and mathematics through their scholarly labour of reading, copying and glossing. Although the processes of learning are often poorly documented, and are often conflated with teaching, it is possible, through close reading of annotations and reconstruction of mathematical processes, to get a glimpse of an individual in the moment of acquiring scientific skills. Focusing on a piece of adaptive copying carried out by an English Benedictine monk c .1380, this article explores the devotional motivations underlying his work, and argues that it was through such copying and compilation that he acquired the expertise necessary to invent an astronomical instrument some years later.